Aspen Aerogels: a capability-based framework for global expansion - Lessard, Donald R. (Henry Stewart Talks, 2018)
This case study applies the RAT/CAT framework to Aspen Aerogels, a company specialising in aerogel-based insulation. By considering the relevance, appropriateness and transferability of its products; Aspen Aerogels internationalised effectively and as of 2014, over 70 percent of its total sales were exports.
Archived at 2024/02/11